Unraveling genetic variations of Dalbergia latifolia (Fabaceae) from Yogyakarta and Lombok Island, Indonesia - Kusumadewi S. Yulita; TIKA D. ATIKAH; WITA WARDANI; SUSILA (Society for Indonesian Biodiversity, 2020)
Abstract. Yulita KS, Atikah TD, Wardani W, Susila. 2020. Unraveling genetic variations of Dalbergia latifolia (Fabaceae) from Yogyakarta and Lombok Island, Indonesia. Biodiversitas 21: 833-841. Dalbergia latifolia Roxb. (Fabaceae) or sonokeling is a timber species extracted for its beautiful heartwood used mainly for musical instruments. D. latifolia was listed in Appendix 2 of CITES since 1997, and the demand for its timber is increasing. The species is considered vulnerable (VU A1cd ver 2.3) to extinction according to the IUCN Red List, while cultivations were mainly done from a root cutting. To anticipate the further loss of population size while maintaining sustainable use of the species, it is essential to evaluate the genetic diversity since the genetic diversity level could serve as an indicator of plant adaptability to its environment. This present study was the first to report the genetic diversity of five populations of D. latifolia from Yogyakarta and Lombok Island, West Nusa Tenggara, Indonesia. Ten combinations of Sequence Random Amplified Polymorphism (SRAP) primers were used to amplify 48 samples of D. latifolia from five populations in Yogyakarta and Lombok Island. The 137 SRAP loci were used for a cluster, and population genetic analysis, with mean NPL, was of 13.6/locus, PLP of 56.18%, H of 0.16, and PIC for all population was of 0.28. The lowest gene diversity (H = 0.11) was observed in population WL 1 of Lombok Island, while the highest (H = 0.20) was recorded for population KP of Yogyakarta. The Yogyakarta and Lombok populations were genetically structured at a medium level (Gst = 0.27), with low genetic distance (0.0310-0.1281), and a moderate level of variation observed among individual trees (ca. 0.5 coefficient similarity). The results of this present study were expected to provide necessary information on further research of D. latifolia from Indonesia to support the sustainable use of D. latifolia in Indonesia and the preservation of this species.